Response of capsicum annuum L. Var. annuum genotypes to root-knot nematode infection - Soares, Renato Silva [UNESP]; Silva, Edgard Henrique Costa [UNESP]; Vidal, Roberta Luiza [UNESP]; Candido, Willame dos Santos; Franco, Carolina Andrade [UNESP]; Reifschneider, Francisco José Becker; Braz, Leila Trevisan [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2018)
Root-knot nematodes are among the main agents that negatively affect the pepper and sweet pepper crop (Capsicum annuum L.), especially Meloidogyne incognita, M. javanica, and M. enterolobii. The objective of this study was to evaluate genotypes of C. annuum L. var. annuum in their response to infection by M. incognita race 3, M. javanica, and M. enterolobii. The experiment was conducted using a completely randomized design arranged in a 27 × 3 factorial scheme with six replicates and each plot consisted of one plant. The experiment was carried out at the UNESP-FCAV in Jaboticabal, São Paulo, Brazil. The genotypes were in plastic pots containing an autoclaved mixture of soil, sand, and bovine manure under greenhouse conditions, and they were evaluated for the reproduction index and reproduction factor at 90 d after inoculation. Thirteen genotypes were classified as resistant, based on the reproductive factor, and highly resistant, based on the reproduction index, to M. javanica, while six were resistant and highly resistant materials to M. incognita race 3. No materials resistant to M. enterolobii were identified. The genotypes CNPH 698, CNPH 701, CNPH 702, CNPH 717, and CNPH 718 were simultaneously classified as resistant to M. incognita race 3 and M. javanica based on the reproduction factor.
Keywords: Hot and sweet peppers; Meloidogyne spp; Reaction; Resistance